Triangulation grids and hierarchical structures of the models in calculation of LED modules - Vitaly, Baynev; Sergej, Fedosin (International Journal of Engineering and Technology, 2018)
The paper considers the problem of designing modern lighting devices and optical systems. Analysis of the development of lighting devices shows that the main stage in their development is the calculation of the optical system. The results of this calculation largely determine the lighting and functional characteristics of light devices. The efficiency of existing methods of calculation are not always satisfied of the development. Application and development of specialized software for the calculation and simulation of light devices significantly facilitates and speeds up the process of their design. The paper presents a mathematical model developed by the software system, described in the hierarchical structure of the simulation geometry LED modules and light devices. Light device in a hierarchical structure represented by the root element of the tree, where the housing, the optical system, a light source, protective glass, suspension assembly, and others are nodes. The affine transformation using to calculate of the absolute position of nodes. The geometry of the nodes is modeled using triangulation grids. To simulate smooth surfaces in a triangulated mesh introduced an additional element - the rib. The software package is carried out modeling of LED optical systems and luminaires based on them using surface models, ray tracing and calculation of photometric body.
Keywords: LED; LED Module; Optical System; Lens; Reflector; Light Device; Calculation; Photometric Body; Program; Hierarchical Structure; Model-ing